Secondary hypnic headache: A literature review in the last 34 years - Fortes, Yasmine Maria Leódido; Erudilho, Eduardo; Silva, Taís Souza da; Souza, Wallyson Pablo de Oliveira; Silva-Neto, Raimundo (Headache Medicine, 2022)
Introduction: Hypnic headache is a rare primary headache disorder that occurs during sleep. Its pathophysiology is uncertain, but hypothalamic dysfunction is hypothesized. It is usually a primary headache, but it can have secondary causes. Objectives: We aimed was to review articles published in the last 34 years on hypnic headache and analyze secondary cases. Methods: Based on a literature search in the major medical databases and using the descriptor “hypnic headache” we included articles published between 1988 and 2020. Of the 359 patients found, only 18 met the inclusion criteria and were analyzed. Results: We found 18 patients (6 men and 12 women) with secondary hypnic headache. The mean age of patients was 58.7±15.0 years, ranging from 20 to 84 years. The causes of hypnic headache were attributed to cranial vascular disorder (five), to non-vascular intracranial disorder (six), to a substance or its withdrawal (three) and to disorder of homoeostasis (four). Conclusions: Although most cases of hypnic headache are primary, some symptomatic cases are described in the literature.